Seleksi Primer LCO – HCO, Primer bird-f1 – HCO Dan Primer bch – bcl Untuk Amplifikasi Gen COI DNA Mitokondria Itik Magelang (Anas javanica) - Setiyawan, Sonny Abdi; Budiharjo, Anto; Kusumaningrum, Hermin Pancasakti (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Magelang duck is a wild type of local duck from Indonesia. The advantagesof Magelangduckcompare tootherlocalduck from Indonesiaareabilityto livein the highlandsandlowlands and high production of egg and meat. Geneticcharacterization of Magelangduck still not available until now.The aim of the research is selectprimers forampliflying COIgeneof mitochondrialDNAof MagelangduckusingLCO-HCO, bird-f1 -HCO, andbcl-bch primers.The research methodwas DNAisolationfrom Magelangduck. Followed by, selection of primer in silicoto find homologywithin COIsequenceusing ClustalX, Genedoc, and FastPCR programs. Amplification of COIgenewas performedusing PCRwith all primerpairs. Result showed partial homology with all primer in COI sequence. TheamplificationusingtheLCO-HCO primer produced primerdimer.Primerbirdf1-HCOand bch-bcl primers showed no amplification. Key words: Magelang duck, COI gene, mitochondrial DNA, primer